2018
DOI: 10.1111/hel.12535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antioxidants on Helicobacter pylori eradication: A systematic review with meta‐analysis

Abstract: The addition of antioxidants (vitamin, N-acetylcysteine, curcumin, cranberry) to amoxicillin-clarithromycin-based therapy could improve the eradication rate, and vitamin supplementation might be effective at a high dosage. However, antioxidant supplements have no impact on improving side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The mechanism of action of dietary antioxidant compounds on H. pylori is not clear. However, the intake of antioxidant-rich nutrients in animals with Helicobacter pylori has been shown to reduce both the number of bacteria in the gastric mucosa and the in ammatory process (8,20). On the other hand, it is possible that these cultivations, by destroying the Iklova factor, have direct antiseptic properties and prevent NF-κβ nuclear transfer, thereby reducing genetic expression and producing mediators associated with relevant in ammation such as TNF-α, IL-1β, IL-6 and IL-8.It is possible that antioxidant-rich nutrient, by controlling some of the toxins that cause enough bacteria to grow by creating special anionic channels in the plasma membrane associated with the release of bicarbonate and organic anions in gastric cells, they have a bene cial effect (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of action of dietary antioxidant compounds on H. pylori is not clear. However, the intake of antioxidant-rich nutrients in animals with Helicobacter pylori has been shown to reduce both the number of bacteria in the gastric mucosa and the in ammatory process (8,20). On the other hand, it is possible that these cultivations, by destroying the Iklova factor, have direct antiseptic properties and prevent NF-κβ nuclear transfer, thereby reducing genetic expression and producing mediators associated with relevant in ammation such as TNF-α, IL-1β, IL-6 and IL-8.It is possible that antioxidant-rich nutrient, by controlling some of the toxins that cause enough bacteria to grow by creating special anionic channels in the plasma membrane associated with the release of bicarbonate and organic anions in gastric cells, they have a bene cial effect (30).…”
Section: Discussionmentioning
confidence: 99%
“…On other hand, Studies suggest that antioxidants (eg, vitamins and N-acetylcysteine) play a role in reducing active oxygen species and gastric in ammation caused by H. pylori, which also exacerbates the disease and prevents the growth of bacteria and eliminates bio lm formation (8). So far, numerous studies have shown that vitamin C and E levels are lower in people with Helicobacter pylori than in those without H. pylori (8). Thus, impaired antioxidant and anti-in ammatory defenses may cause or exacerbate a chronic condition of pyloric H infection.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that N‐acetylcysteine plays a protective role in H pylori ‐related diseases . We investigated the efficacy and safety of adding antioxidants to triple or quadruple therapy and showed that the addition of antioxidants to amoxicillin‐clarithromycin‐based therapy could improve the eradication rate . However, antioxidant supplements have no impact on improving side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of H pylori eradication has steadily declined, primarily because of antibiotic resistance . Our previous studies have shown that the addition of antioxidants, such as vitamins, N‐acetylcysteine, curcumin, and cranberry, to amoxicillin‐clarithromycin–based therapy could improve the eradication rate …”
Section: Antioxidants: a New Strategy For Helicobacter Pylori‐relatedmentioning
confidence: 99%
See 1 more Smart Citation